Reliability of reporting the presence of transformation zone material in Papanicolaou smears using an automated screening system - (:unkn) unknown (WILEY, 2017)
Objective: This study was conducted to evaluate the reliability of using an interactive automated screening system (IAS) to determine the presence of endocervical and/or metaplastic cells (transformation zone material; TZM) in liquid-based cytology (LBC) Papanicolaou (Pap) smear slides. Materials and methods: A series of LBC Pap smears was manually screened to determine the presence or absence of TZM. The results were compared to those obtained through IAS. Results: ThinPrep (R) Imaging System (Imager)-assisted screening indicated that 22.4% of the slides did not contain TZM in cases in which previous manual screening revealed that 100% of the slides did contain TZM. Conclusion: The reliability of determining TZM through IAS is limited. Manual screening of the slides appears to be necessary to report the presence of TZM accurately.
Keywords: automated screening system; Pap smear; endocervical cells; Papanicolaou smear; liquid based; transformation zone material; THINPREP IMAGING-SYSTEM; CERVICAL CYTOLOGY; CANCER; ACCURACY; LESIONS